Factors Influencing the Adoption of Contact Tracing Applications: Systematic Review and Recommendations - Oyibo, Kiemute; Sahu, Kirti Sundar; Oetomo, Arlene; Morita, Plinio Pelegrini (Frontiers in Digital Health, 2022)
The emergence of new variants of COVID-19 causing breakthrough infections and its endemic potential are an indication that digital contact tracing apps (CTAs) may continue to be useful for the long haul. However, the usage of these apps in many countries around the world has not been encouraging due to several factors militating against their adoption and usage. In this systematic review, we set out to uncover the key factors that facilitate or militate against the adoption of CTAs, which researchers, designers and other stakeholders should focus on in future iterations to increase their adoption and effectiveness. Seven databases, including PubMed, CINAHL, Scopus, Web of Service, IEEE Xplore, ACM Digital Library, and Google Scholar, were searched between October 30 and January 31, 2020. A total of 777 articles were retrieved from the databases, with 13 of them included in the systematic review after screening. This review identified 13 relevant articles, which found 56 factors that may positively or negatively impact the adoption of CTAs. Of the 56 factors, privacy concern turned out to be the most frequent factor of CTA adoption (12/13), followed by perceived benefit (7/13), perceived trust (6/13), and perceived data security risk (6/13). The identified factors were thematically grouped into ten categories: privacy and trust, app utility, facilitating conditions, social-cognitive influence, ethical concerns, perceived technology threats, perceived health threats, technology familiarity, persuasive design, and human/demographic factors. The results suggest that future CTA iterations should give priority to privacy protection through minimal data collection and transparency, improving personal and social benefits, and fostering trust through laudable gestures such as delegating contact tracing to public health authorities, making source code publicly available and stating who will access user data, when, how, and what it will be used for. Moreover, the results suggest that data security and tailored persuasive design, involving reward, self-monitoring, and social-location monitoring features, have the potential of improving CTA adoption. Hence, in addition to addressing issues relating to utility, privacy, trust, and data security, we recommend the integration of persuasive features into future designs of CTAs to improve their motivational appeal and the user experience.